2022
DOI: 10.1021/acsaem.2c02421
|View full text |Cite
|
Sign up to set email alerts
|

Account of Ni/NiO Nanoparticle-Supported N-Doped Graphitic Carbon Derived from Sugarcane Waste as a Sustainable Electrocatalyst for Oxygen Evolution Reaction

Abstract: The recent past has witnessed an exponential increase in the demand for energy conversion, storage, and consumption technologies. The development of inexpensive, efficient, durable electrode materials and catalysts is critical to the success of these technologies/devices. Here, we present a simple, sustainable, cost-effective, and scalable method for preparing stable and effective nickel/nickel oxide nanoparticles on highly porous Ndoped graphitic carbon. The catalysts were prepared by a direct pyrolysis metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Fig. 8f summarizes the performance of the EG30 prepared in this study compared to the NiO/Ni/C 8–10,38–44 and noble metal 45,46 previously reported in literature. Herein, we mainly compare overpotentials and Tafel slopes.…”
Section: Resultsmentioning
confidence: 94%
“…Fig. 8f summarizes the performance of the EG30 prepared in this study compared to the NiO/Ni/C 8–10,38–44 and noble metal 45,46 previously reported in literature. Herein, we mainly compare overpotentials and Tafel slopes.…”
Section: Resultsmentioning
confidence: 94%
“…KCl) and Platinum foil has been used as reference and counter electrodes respectively in all these experiments, whereas diverse methods have been tried for loading the electrocatalyst on PCE, based on its nature. Ru‐triazine COF, [51] Ni based MXene, [89] hierarchical nanostructure, [90] and Ni‐doped graphitic carbon based electrocatalysts [91] were loaded in the blends of nafion by drop casting. On the other hand, hierarchical polyoxometallate thin film has been directly picked up from the air‐water interface [73] .…”
Section: Pce As Multipurpose Electrode Platformmentioning
confidence: 99%
“…As we have reported in our previous report, sugarcane waste was used as a biomass precursor for the synthesis of graphitic carbon doped with nitrogen and Ni NPs were encapsulated with a graphitic shell giving good catalytic activity. 13…”
Section: Introductionmentioning
confidence: 99%
“…As we have reported in our previous report, sugarcane waste was used as a biomass precursor for the synthesis of graphitic carbon doped with nitrogen and Ni NPs were encapsulated with a graphitic shell giving good catalytic activity. 13 In this work, we report an electrochemical method for the production of green hydrogen using a combination of an innovative catalyst, electrolyte, and electrode platform. Among various catalysts developed, the Ni-based catalyst assures an acceptable high performance and low cost as compared to previous metal-based catalysts.…”
Section: Introductionmentioning
confidence: 99%